Relationship Between Brand Equity And Consumer Purchase Decision: A Case Of An International Brand Of Footwear - Fadilah, Siali; Pang, Jiayi; Mahani Mohammad, Abdu Shakur; Siti Aisyah, Ya’kob (Universiti Teknologi MARA, 2016)
Footwear has immense effects on the fashion industry and goes beyond fashion to cater to other functions such as sports, office, urban streets and technical outdoor. The objective of the study is to discover the relationship between brand equity and consumer purchase decision in an international brand of footwear. There are four elements in the brand equity model which are brand awareness, perceived quality, brand association, and brand loyalty. A total of 384 young adults participated in this study. In order to test the hypotheses, correlation coefficient was applied to identify the relationship between brand equity elements and consumer purchase decision in an international brand of footwear. The results suggest a noteworthy relationship between brand equity and purchase decision and the most significant determinant of brand equity is perceived quality. Hence, sustainable brand equity is significantly associated with consumer purchase decision in an international brand of footwear.